2018
DOI: 10.1534/g3.117.300370
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Validation of a New Source of Low Grain Cadmium Accumulation in Durum Wheat

Abstract: Cadmium (Cd) is a heavy metal that has no known biological function and is toxic for many living organisms. The maximum level of Cd concentration allowed in the international market for wheat grain is 0.2 mg kg−1. Because phenotyping for Cd uptake is expensive and time consuming, molecular markers associated with genes conferring low Cd uptake would expedite selection and lead to the development of durum cultivars with reduced Cd concentrations. Here, we identified single nucleotide polymorphisms (SNPs) associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 45 publications
0
17
0
Order By: Relevance
“…5AL in a region homeologous to the Cdu1 locus by using genome-wide association scans. Recently, Oladzad-Abbasabadi et al (2018) reported that a novel locus for Cd uptake in grain (Cdu2-B), which was transferred from common wheat into the durum wheat background, is close to (Miyadate et al 2011, Sasaki et al 2014, Satoh-Nagasawa et al 2012, Ueno et al 2010, Yamaji et al 2013. In durum wheat, TdHMA3-B1, which is located within a 0.14 cM interval on Chr.…”
Section: Discussionmentioning
confidence: 99%
“…5AL in a region homeologous to the Cdu1 locus by using genome-wide association scans. Recently, Oladzad-Abbasabadi et al (2018) reported that a novel locus for Cd uptake in grain (Cdu2-B), which was transferred from common wheat into the durum wheat background, is close to (Miyadate et al 2011, Sasaki et al 2014, Satoh-Nagasawa et al 2012, Ueno et al 2010, Yamaji et al 2013. In durum wheat, TdHMA3-B1, which is located within a 0.14 cM interval on Chr.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, molecular breeding approaches have accelerated progress in breeding low-Cd cultivars by exploiting technologies such as marker-assisted selection, allele discovery, allele pyramiding, genome mutation, genome selection, genome-wide association mapping, and gene editing. The adoption of novel technologies, such as genetic modification, markerassisted selection, and gene editing, has received increasing interest (Randhawa et al, 2013;Oladzad-Abbasabadi et al, 2018). Furthermore, the successful integration of molecular breeding with conventional breeding methods will accelerate the development of low-Cd cultivars.…”
Section: Methodologies For Breeding For Low-cd Cultivarsmentioning
confidence: 99%
“…Thus, more attention and effort have been paid to breeding low-Cd durum wheat than bread wheat. Several dozen low-Cd durum wheat cultivars have been identified worldwide (Eriksson, 1990;Grant et al, 2008;Arduini et al, 2014;Zimmerl et al, 2014;Kubo et al, 2016;Perrier et al, 2016;Hirzel et al, 2017Hirzel et al, , 2018Vergine et al, 2017;Oladzad-Abbasabadi et al, 2018;Yue et al, 2018).…”
Section: Genetic Differences and Screening For Low-cd Cereal Cultivarmentioning
confidence: 99%
“…Different categories of molecular markers were used for tagging the marker-QTL of Cd resistance in wheat (Table 2). A major QTL (designated QCdu.ndsu-5B) of Cd uptake on chromosome arm 5BL within a 0.3 cM distance in durum wheat was identified with SNP markers [77]. Similarly, Penner et al (1995) detected a dominant random amplified polymorphic DNA (RAPD) marker (OPC-20) for low Cd uptake in western Canadian durum wheat [88].…”
Section: Marker-quantitative Trait Loci (Qtl) Analysis For CD Toxicitmentioning
confidence: 97%
“…The recent advancements in molecular genetics knowledge have established many modern breeding methods to confer Cd resistance in wheat. Progress in wheat against Cd stress continues by exploiting molecular breeding tools, such as marker-assisted selection, allele discovery, allele pyramiding, genome mutation, association mapping, genome selection, and next-generation sequencing [77]. Currently, there are two key molecular approaches to assess Cd stress in wheat: marker-assisted selection and genomic selection [78].…”
Section: Breeding Strategies For Low-cd Wheat Cultivarsmentioning
confidence: 99%